The “Cognitive experience, area of business, responsiveness and engagement” conceptual framework for integrated reporting - Abdul Hamid, Fathilatul Zakimi; Shafie, Rohami; Othman, Zaleha (American Scientific Publishers, 2015)
The purpose of this paper is to propose a conceptual framework for integrated reporting (IR).Accountability and governance are two fundamental concepts embedded in the framework, which aims to complement existing IR frameworks developed by institutions.We label this framework “CARE”, abbreviated from Cognitive Experience, Area of Business, Responsiveness and Engagement. The proposed framework considers financial reporting as a continuous process, aiming to reflect integrated thinking by management for the long-term survival of a business, rather than focusing on short-term performance, which may result in unsustainable business development. Implicitly, it will enhance accountability and transparency in business operations.It also proposes altering the managerial perspective from a “license to operate” to a “license to sustain.”